2022
DOI: 10.18697/ajfand.115.22520
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of food and nutrition security status of Nigeria preschool children towards achieving the Sustainable Development Goals 1,2,3 - A review

Abstract: Child nutrition is essential to any country's food and nutrition security status. It goes beyond food security to encompass all the components of child well-being and cognitive development. It includes infant and young child feeding practices, care practices, and hygiene. Africa accounts for the highest prevalence of child malnutrition and mortality worldwide. The complexity and interconnectedness of the components of child nutrition in developing countries are yet to be well conceptualized. Due to a high pove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The absence of balanced diets is exhibited in various forms of malnutrition which encompass undernutrition and overnutrition and is known as the triple burden of malnutrition; the coexistence of undernutrition (shown by wasting and stunting), micronutrient deficiencies (often regarded as hidden hunger), and overnutrition (overweight and obesity) (Omachi et al, 2022).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The absence of balanced diets is exhibited in various forms of malnutrition which encompass undernutrition and overnutrition and is known as the triple burden of malnutrition; the coexistence of undernutrition (shown by wasting and stunting), micronutrient deficiencies (often regarded as hidden hunger), and overnutrition (overweight and obesity) (Omachi et al, 2022).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…Several underlying causes of malnutrition in resourced and under-resourced countries, including South Africa, are associated with poverty as the leading cause. A high proportion of poverty has been reported in KwaZulu-Natal (KZN) (Govender et al, 2017;Omachi et al, 2022). An evaluation of food and nutrition insecurity of households in some selected rural communities in KZN, South Africa, showed that about 47% to 53% of black South Africans are disadvantaged (Govender et al, 2017).…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
See 2 more Smart Citations